Evaluation of extension initiative to support micro enterprises and small businesses - Cristo Sant Anna, Hugo; Aragão Costa de Oliveira, Tarsila; Broedel Silva Nunes, Fabrício; Zaneti Zucarato, Isabela; Dutra do Souto Gatti, Giordana; Bins Gomes, Rodrigo; Vargas Marçal, Monica; Florêncio Lobo, Henrique (Guará Journal, 2019)
The gradual adoption of Design may contribute to the improvement of competitiveness of firms, specially in moments of economic crises like the one faced by Brazil since 2015. Nonetheless, previous studies suggest there would be a lack of information about potential contributions  from  designers  on  business  image  and management.  This  paper  aims  to  evaluate  the extension  event  Dia  D,  which  offered  free  free guidance  on  academic  disciplines  studied  at  the Design  Undergraduate Course at Universidade Federal do Espírito Santo Uf to  Micro  Enterprises  and  Small Businesses  (MESBs)  The  analysis  of  data  collected during  guidance  indicated  the  main  demands  and challenges  for  MESBs  which  attended  the  event according  to  their  industry, suggesting opportunities for future research and extension activities. Results also contribute to the improvement of teaching, in that  they evidence  themes  which  could  be  discussed  at  the Design  Undergraduate  Course  and  in  its  interaction with  other  courses  at  Ufes,  bringing  students  close to  the  reality  of  the  labour  market  in  Espírito Santo.
Keywords: Design; Extension; Entrepreneurship